Analisis Efektivitas Biaya Terapi Antihipertensi di Indonesia: Systematic Literature Review Berdasarkan Parameter ACER dan ICER Periode 2019–2024”: - - honifa; Cyntia wulandari (Journal Pharma Saintika, 2025)
This study aims to systematically review the literature analyzing the cost-effectiveness of antihypertensive therapy in Indonesia for the 2019–2024 period and to identify the most cost-effective regimens based on Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The systematic review was conducted following the PRISMA 2020 guidelines, with literature searches performed on PubMed, Google Scholar, and ScienceDirect using the keywords “cost-effectiveness,” “antihypertensive,” “ACER,” “ICER,” and “Indonesia.” Selected articles were assessed for relevance, data completeness, and methodological quality.The findings indicate that therapies based on Calcium Channel Blockers (CCB), particularly amlodipine, and the combination of ACE inhibitors (ACEI) + CCB, are the most cost-effective regimens compared to Angiotensin Receptor Blockers (ARB), diuretics, and branded drugs. These regimens provide higher clinical effectiveness at a lower treatment cost, especially among patients with uncomplicated hypertension or comorbid diabetes mellitus. Furthermore, the use of generic drugs consistently demonstrated lower ICER values compared to branded products, supporting cost-efficiency policies under Indonesia’s National Health Insurance (BPJS Kesehatan). These findings may serve as a foundation for developing the National Formulary and cost-efficient drug procurement policies. Limitations include the narrow range of studies and the absence of Quality-Adjusted Life Years (QALY) and indirect cost analyses, suggesting future research should adopt a multicenter cost-utility approach for more comprehensive evaluation